PENGARUH PEROKOK TERHADAP ADANYA C – REAKTIVE PROTEIN (CRP) - F. Pramonodjati; Anggraeni Sih Prabandari; Francisko Angelo Eko Sudjono (Universitas Duta Bangsa Surakarta, 2019)
Cigarettes are packaged tobacco products including cigars or other forms of Nicotiana tabacum, Nicotiana rustica or their synthesis. Three main toxic agents in cigarette are Nicotine, Tar and Carbon monoxide. Their toxin activities can damage cell, tissue. Lugs and cardiovascular system are the main organ affected due to inflammatory reaction caused by its toxin. Specific proteins was produced in the liver responsed tissue damage and inflammation, one of them is C-Reactive Protein (CRP). We conducted research to measure CRP level in blood serum of active smokers and whether its correlation to long term smoking and number of cigarettes consumed. Fourty (40) men apparently health, have been smoking for more 6 years, have no symptom of cardiovascular disease and other chonic disease was participated in this reseach. CRP was analized by Quantitative Latex Aglutination Method. Descriptive data analysis shows average number of cigarettes consumed every day is 10,70 and duration of smoking is 8,67 years. Statistic analysis obtained no correlation of long term smoking and number of cigarettes consumed to CRP level (r = 0.057 and r = 0.729 respectively).